THE CIDR1Î±-PfEMP1 SEQUENCE FROM INDONESIAN PLASMODIUM FALCIPARUM AND ITS POTENTIAL ASSOCIATION WITH THE CEREBRAL OUTCOME - Sulistyaningsih, Erma; Armiyanti, Yunita; Dewi, Rosita (MNJ (Malang Neurology Journal), 2021)
Background: Plasmodium falciparum Erythrocyte Membrane Protein 1 (PfEMP1) is an important protein responsible for the pathogenesis of severe malaria, including cerebral malaria. The protein is highly diverse. The CIDR1Î±-PfEMP1 binds endothelial protein receptor (EPCR) and may associated with the brain swelling in childhood malaria.Objective: To analyze the CIDR1Î±-PfEMP1 from Indonesian isolate and determine its association with cerebral malaria outcome.Methods: Fifteen blood samples of clinically mild to severe malaria-patient were collected for DNA extraction. Malaria diagnosis was conducted microscopically by Giemsa-stained thin blood smear. The CIDR1Î± domain was amplified by PCR using specific primer and PCR product was sequenced. The nucleotide sequences were analyzed by NCBI blast, DNASIS MAX 3 and translated into amino acid sequences using Expasy Translation Tool.Results: One out of fifteen samples was severe malaria case and infected with P.Â  falciparum, the rest were clinically mild to moderate malaria and infected with pure P. falciparum or mixed infection of P. falciparum and P. vivax. Amplification for CIDR1Î± domain resulted a single band of + 550 bp from a severe sample only. Sequencing of PCR product on both strands read 524 nucleotides and BLAST analysis confirmed as CIDR1Î± sequence. Multiple alignment showed 74-78% nucleotide sequence similarity with reference sequences, but amino acid sequences presented 23.5% homologous.Conclusion: An identified CIDR1Î± domain only from severe case implicating the potential association with the severe outcome including cerebral malaria, but the highly diverse of the domain needs further studies on the interaction with the pathological-causing receptor in the host.Â